Challenges in Providing Gynecological Procedures in Primary Care: A Survey of Canadian Academic Family Physicians - Parisa Rezaiefar; Douglas Archibald; Monisha Kabir; Susan Humphrey-Murto (Women's Health Reports)
Purpose: Globally, there is a lack of access to health care providers who offer gynecological procedures. Understanding the practice patterns of academic family physicians (AFPs) and whether additional training impacts the provision of care is critical. This study surveys the practice patterns of AFPs regarding gynecological procedures offered, identifies barriers, and explores the impact of additional training. Methods: We circulated an anonymous, cross-sectional survey to all 17 family medicine programs across Canada, receiving responses from 71 AFPs. We computed descriptive statistics and bivariate associations. Results: A total of 71 respondents from five universities participated. Most participants (97.2%) performed Papanicolaou (Pap) smears; 67.6% provided intrauterine device (IUD) insertion, and only 54.9% offered endometrial biopsy. Numbers decreased significantly for routine pessary care (29.5%), punch biopsy of the vulva (15.5%), and pessary fitting (5.6%). Eighteen participants (26.9%) had received enhanced skills training with a certificate of added competence (CAC), of which 55.6% were in women’s health. CAC holders in women’s health provided IUD insertions (100% vs. 67.3%; p = 0.049, V = 0.28) and endometrial biopsies (90.0% vs. 53.1%; p = 0.036, V = 0.28) at higher rates than general AFPs. Frequently cited barriers to offering gynecological procedures included lack of knowledge, procedural skills, and insufficient patient volumes to maintain competence. During the COVID-19 pandemic, 44% of respondents reported reducing or ceasing to provide Pap smears. Conclusions: Many AFPs in Canada do not provide essential gynecological procedures. This impacts patient access and the training of the next generation of family physicians and thus requires innovative strategies to address the persistent procedural skills educational gap for trainees.